A NEW METHOD FOR TECHNICAL DIAGNOSTICS OF DIESEL ENGINE CYLINDER - Ivan Mavrin (Promet - Traffic&Transportation, 1970)
In this paper the possibility of application of the cylinderdiagnostics on vibrarion basis is given. A new method is defined.It shows advantages in comparison to the other knownmethods. The influence of various pressures in Ihe cylinder andthe influence of engine working cycle on determining of thecylinder wear are analyzed The theoretical assumptions andexperimental results have proved that this method is a newpossibility for defining the tec!VIical state of the cylinder withoutbeing disassembled, especially suitable for the practicalapplication.